Pemenuhan Hak Pendidikan Warga Negara Miskin di Indonesia - Faujiah; Arifuddin; Fahmi Parmansyah (Jurnal LENTERA: Jurnal Studi Pendidikan, 2023)
Poverty is the most common problem faced by developing countries like Indonesia, this problem causes the high dropout rate for poor citizens. The right to education for poor citizens must be fulfilled by the government as an implementation of the contents of the constitution. This article uses the literature study method with data collection techniques by collecting journals, books, websites. Data analysis is done by reading about the references needed in finding data and making sentences. Education has a strong correlation with poverty, education affects the level of permanent income of every citizen so that it can reduce poverty. To acquire knowledge and skills in general, use education. The government is obliged to prosper its citizens in the field of education so that citizens can find a way out of the poverty they face. In addition, the government must be able to make policies that empower the community and ensure the implementation of these policies properly.